Online stakeholder engagement to bridge the science-policy interface for marine pollution research: adaptation & evaluation of the focused conversation method and ORID framework - Kathrin Kopke; Sonya Agnew; Orla-Peach Power (Discover Oceans)
Abstract This paper introduces an online adaptation of the Focused Conversation Method (FCM), demonstrating through three marine pollution projects how structured online stakeholder dialogues can inform research and support informed decision-making. The approach involved applying an ORID Framework (Objective, Reflective, Interpretive, and Decisional) implemented in six online workshops (2 per project) to engage scientists, policy experts, decision makers, research funding agencies and industry representation with focus on underwater noise (JONAS), microplastics analyses of seawater samples (ANDROMEDA), and evidenced based science communication on microplastic pollution (RESPONSE). Results demonstrated that the method could be successfully implemented to maintain high quality interactions in online environments, and facilitated structured, inclusive discussions that generated actionable recommendations tailored to each project’s objectives. Participant feedback underscored the value of structured dialogue for enhancing collaboration and producing tangible outputs. The findings demonstrate the adaptability of the ORID framework and its effectiveness in online settings, offering a robust tool for stakeholder engagement. By fostering meaningful dialogue, balancing structure with flexibility, and integrating feedback for continuous improvement, the study demonstrates that online stakeholder engagement can greatly contribute to bridging the gap between marine research and relevant policy development in a meaningful way. The work underscores the importance of structured methods for advancing research relevance, influencing policy, and fostering collaboration across disciplines and sectors, with recommendations for future online stakeholder engagement strategies.